Thermal, Magnetic Properties and Antimicrobial Effects of Magnetic Iron Oxide Nanoparticles Treated with Polygonum cognatum - Pekdemir, Mustafa Ersin; Pekdemir, Sibel; Inci, Sule; Kirbag, Sevda; Ciftci, Mehmet (Springer Int Publ Ag, 2021)
This study aimed to synthesize magnetic Fe3O4 nanoparticles treated with Polygonum cognatum and then evaluate its thermal, magnetic, and antimicrobial activity. The surface morphology of MNP was characterized by SEM and image mapping. The XRD measurements were carried out to calculate the crystallite size of the sample, and the cubic structure of the iron oxide nanoparticles was identified in the XRD pattern. FT-IR spectroscopy confirmed that the bioactive molecules in the plant structure are attached to the MNP surface. Thermal analysis showed that the plant extract reduced the thermal stability of pure MNP. From the magnetization curves obtained by VSM, it was seen that MNP treated with the plant has superparamagnetic properties and its saturation magnetization value is 26.073 emu/g. Besides, the antimicrobial effects of MNP, plant extract, and MNP treated with plant extract against Staphylococcus aureus, Klebsiella pneumoniae, Escherichia coli, Bacillus megaterium, and Candida albicans were examined.
Keywords: Fe3O4 nanoparticles; Polygonum cognatum; Antibacterial; SEM; Thermal